Case Report: Giant Pelvic Cystic Appearance—An Unusual Feature of Uterine Cervical Adenocarcinoma - Wang, Yongxin; Shan, Xue; Li, Man; Yue, Ying (Frontiers in Surgery, 2022)
Cervical adenocarcinoma can present as a solid, mixed solid, cystic, or multiple cystic cervical mass in the endocervical canal. In this report, we present an extremely rare case of cervical adenocarcinoma with giant cystic lesions. A 37-year-old Chinese woman with a regular menstrual cycle presented to her local doctor complaining of mild abdominal distension. Abdominal ultrasonography suggested an ovarian cyst, whose mean diameter increased from 3 to 8 cm in 3 months. Thereafter, she was referred to our hospital. She had no abnormal vaginal bleeding or discharge. Transvaginal ultrasonography revealed a 95 × 80 mm cyst below the back of the uterus. Computed tomography revealed a 9.8 × 8.5 cm multilocular cyst between the cervix and right ovary. Human papillomavirus (HPV)-E6 and -E7 mRNA tests revealed HPV-16 positivity. The thin-layer, liquid-based cytological test of the cervix showed negative results. No tumor lesions were observed on the cervical biopsy histopathology. The lesion was misdiagnosed as an ovarian cyst prior to the surgery. Intraoperatively, a cyst of the size of a child's head was observed extending from the low posterior wall of the uterus to the posterior lip of the cervix, and the cervical cysts were resected. Histological examination revealed cervical adenocarcinoma. Subsequently, she underwent extensive hysterectomy, bilateral salpingectomy, and pelvic lymphadenectomy. The final diagnosis was stage IB3 cervical adenocarcinoma. After 21 months of follow-up, no clinical or radiological evidence of recurrence has been found.